P22 Phenytoin versus levetiracetam for post traumatic brain injury seizure prophylaxis; a retrospective study at a UK major trauma centre. Issue 3 (14th February 2019) - Harris, L; Hateley, S; Seemungal, B
Abstract : Objectives: 12% of patients with severe Traumatic brain injury (TBI) suffer from seizures. Evidence suggests that the use of an antiepileptic drug (AED) is beneficial in preventing early post TBI seizures. To date, no specific NICE guidelines exist on the choice of post TBI seizure prophylaxis. This study aims to identify the trend in AED usage, the impact on length of stay and to compare the tolerability of phenytoin and levetiracetam. Design: Retrospective observational study. Subjects: 201 patients. Methods: All patients admitted to a Major Trauma Unit following a head injury treated with levetiracetam or phenytoin for seizure prophylaxis were included in the study. Data was collected between October 2013 – September 2014 and November 2016 – October 2017. Patient demographics, Glasgow Coma Score (GCS) on admission, length of treatment, AED toxicity, length of stay, complications, surgical input and length of ITU stay were recorded. Results: 85.6% of patients were treated with phenytoin in 2013–2014% and 82.5% were treated with levetiracetam in 2016–2017. The average length of stay for phenytoin was 23.2 days and 13.9 days for levetiracetam. Subgroup analysis was performed on patients with an admission GCS of 14–15. Length of stay for phenytoin was 14.9 days (SD −11.87) and levetiracetam 9.4 days (SD 10.588) (p=0.07). 24% of patients on phenytoin and 14% on levetiracetam suffered from dizziness. Conclusions: This suggests that levetiracetam is tolerated better with fewer side effects. We recommend its use in clinical practice.